Pengaruh Pembiayaan Gadai Emas dan Pembiayaan Ar-rum Terhadap Perolehan Laba Pegadaian Syariah - Nana Diana (UNSIKA (Universitas Singaperbangsa Karawang), 2016)
Pegadaian Sharia as a formal financial institution in the form of of Perum Pegadaian unit in Indonesia, which served to channel financing in the form of cash loans to people in need is based on sharia law lien is a matter that needs to get a positive response. In the most important Pegadaian Syariah is able to provide in accordance with the expected benefit society and eschew practices usury', qimar (speculation), and gharar (transparation). If seen from the main objective of more mashlahat capable of being a major capital Pegadaian Syariah getting customers to be able to channel gold mortgage financing (Ar-Rahn) and Ar-Rum financing that affect the company's profit Pegadaian Sharia. This study aimed to analyze the effect of mortgage financing gold to profit Pegadaian sharia, analyze Influence Financing Ar-Rum towards profit earnings Pegadaian Syariah, analyze Effect of partially financing Gold Pawn Against Financing Ar-Rum on Pegadaian Sharia and to analyze Influence Simultaneous Financing Pledge gold and Financing Ar-Rum towards profit earnings Pegadaian Sharia.The company can be viewed as a system that processes the inputs to produce outputs. Companies try to produce output that is higher than the value of the input in order to generate profits. Based on previous research and theories there are several factors that influence profitability including financing amount. This research has the framework in gold mortgage financing independent variable (Ar-Rahn) as a variable (X1) and Financing Ar-Rum as a variable (X2) effect on the dependent variable, namely profit companies pegadaian sharia (Y).This study population is data in the annual report published 2010-2014. The data in this study are included in the periodic data or time series and data collection using archival research and observations directly to the headquarters of PT Pegadaian (Persero). Answer the problems and hypothesis of the study used qualitative analysis techniques using classical assumption test. Engineering and analysis is performed with the aid ofa software program SPSS version 16. The results showed the number of mortgage financing gold (Ar-Rahn) has a significant positive effect on profit in the amount of 95.2%. While the amount of financing Ar-Rum has a positive effect though not too significantly by 29%. Number of mortgage financing gold (Ar-Rahn) and the amount of financing Ar-Rum simultaneously have a positive and significant impact on the profit is equal to 99%.